Aleksander Puszkin a almanach „Mnemozyna” - Bezwiński, Adam (Rusycystyczne Studia Literaturoznawcze, 2016)
Between 1824 and 1825, the group of Russian Schelling scholars, with Wilhelm Küchelbecker, were publishing Mnemosyne periodical, which had covered aesthetics, philosophy, and a literary section. In the last part, Alexander Pushkin published five of his works (two of them included sheet music), two of which remain his most significant works of this period: Demon and To the Sea. A discussion and a protest were incited by the introductory essay by Küchelbecker, On the Course of Our Poetry, especially the lyrical one written in the preceding decade. In his response, Pushkin opposed the literary preferences of the editor, who had been privileging classicist genres: ode and tragedy. Pushkin, against him, affirmed and defended the romantic tendencies.